(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
Educationis the doorway to the wider world & an exposition on rural infrastructureis incomplete without an assessment of the extent to which we have been able toopen this door for the children of rural India. Rural education plays a pivotalrole in the development of the country as a whole because majority of thepopulation live in rural areas.